2016
DOI: 10.1002/lom3.10110
|View full text |Cite
|
Sign up to set email alerts
|

Growth bands are an unreliable indicator of sea urchin age: Evidence from the laboratory and the literature

Abstract: Knowledge of urchin age structure is crucial for understanding their ecosystem impacts and improving their management. In sclerochronology, translucent and opaque growth bands (TGB, OGB) in urchin ossicles are used to estimate age. An essential premise for using this technique is that one TGB and one OGB are formed every year, independent of urchin size or ossicle type. TGB and OGB addition are associated with slow and fast growth, respectively, and assumed to be added seasonally due to changes in water temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Validation of ageing in non-Ellisellidae octocorals cannot be assumed to apply to sea pens. In absence of validation data from ellisellids and sea pens we concur with Narvaez et al (2016), who caution against interpreting growth rings as annual. This is reinforced by our observations of the presence of lighter rings in some sections that if counted could triple the maximum age recorded.…”
Section: Discussionsupporting
confidence: 61%
“…Validation of ageing in non-Ellisellidae octocorals cannot be assumed to apply to sea pens. In absence of validation data from ellisellids and sea pens we concur with Narvaez et al (2016), who caution against interpreting growth rings as annual. This is reinforced by our observations of the presence of lighter rings in some sections that if counted could triple the maximum age recorded.…”
Section: Discussionsupporting
confidence: 61%
“…for using this technique is that a complete cycle (one translucent or dark ring and one opaque or light ring) is added each year (or following any other quantifiable periodicity), independent of individual size. However, these assumptions are not unanimously supported by experiments and their accuracy remains open to discussion [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is worth noting that other factors could be included in the sampling plan, such as the size-feeding relationship [27]; seasonality, gonadal development and reproductive status [10]; feeding differences and growth [12]; abundance [5]; life history parameters [11]; other environmental factors; and the plan's possible effects on re-population techniques [28]. In addition, the detection of the selective fishing pressure effects allow studying the life history parameters of exploited sea urchins under more natural conditions [12].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, almost 50% of the total landings come from the area around Chiloé Island (41 • 47 S-43 • 28 S), which is separated from the mainland on its northern edge by Chacao Channel (∼41 • 47 S) and to the south by Chonos Archipelago (43 • 50 S-45 • 45 S) ( [1,8,9]; see Figure 1). Studies by Balboa et al [7] showed that sea urchin is being harvested under selective fishing pressure (and selective predation on females in Quellón [10]), which suppresses growth rates (see also [4,11]). Individual growth patterns and genetic effects on populations can lead to density-dependent and trophic consequences observed in benthic species and compensatory growth.…”
Section: Introductionmentioning
confidence: 99%